Tuberculosis in foreign students in Japan, 2010–2014: a comparison with the notification rates in their countries of origin - Masaki Ota; Kazuhiro Uchimura; Seiya Kato (Western Pacific Surveillance and Response, 2016)
This study characterizes the foreign students with tuberculosis (TB) registered in Japan from 2010 to 2014 and compares their TB notification rates with those in their countries of origin. The TB notification rates in foreign students were retrieved from the National Epidemiological Surveillance of Infectious Disease system in Japan. National TB notification data from 16 countries and areas were extracted from the World Health Organization’s and the official health websites of the countries and areas.